Fraud reporting in Catalonia in the Internet era: Determinants and motives. (September 2022) - Kemp, Steven
Fraud has been identified as one of the most prevalent property crimes in the Internet era and underreporting represents one of the most pressing challenges to prevention and policing. Like fraud itself, the issue is not new and therefore traditional findings and approaches designed to foster reporting may also be applicable to online fraud. This study performs a series of regression models to analyse data on fraud victims from two editions of the representative Catalan Public Security Survey. The aim is to identify and compare socio-demographic, context and crime event determinants of online and offline fraud reporting, as well as the reasons for not reporting. Thus, the article contributes to the literature regarding cybercrime and traditional crime a/symmetries. The findings show that, surprisingly, online fraud is reported at a higher rate than offline fraud, mainly owing to the greater odds of being considered a crime by the victim. In general, fraud reporting appears to involve a rational component because financial and non-financial harms and the expected utility of reporting are more relevant to the decision than socio-demographic factors. In addition, the most common reasons for not reporting refer to the opportunity costs of doing so. The demographic predictors of online reporters show only slight differences from their offline counterparts, but more associations are found regarding the reasons for not reporting. Finally, the implications for policy are discussed.